2017
DOI: 10.21815/jde.016.020
|View full text |Cite
|
Sign up to set email alerts
|

Student Self‐Assessment of Operative Dentistry Experiences: A Time‐Dependent Exercise in Self‐Directed Learning

Abstract: The aim of this study was to evaluate the process of student self-assessment on operative dentistry skills across four years at the University of Louisville School of Dentistry. First, a retrospective analysis of the Class of 2016 students' self-assessment and faculty assessment grade sheets was conducted to determine mean differences and correlations across time. Both preclinical (D2: n=120) and clinical (D3: n=120; D4: n=120) grade sheets were evaluated. Second, 25 students from each of the D1, D2, D3, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…When examining dental education, our previous studies have shown that there is significant room for improvement in student's self‐assessment ability during their preclinical years 1,6 . Various studies have investigated students’ self‐assessment skills and found discrepancies between the levels of competence perceived by preclinical students, clinical students, and faculty 4,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…When examining dental education, our previous studies have shown that there is significant room for improvement in student's self‐assessment ability during their preclinical years 1,6 . Various studies have investigated students’ self‐assessment skills and found discrepancies between the levels of competence perceived by preclinical students, clinical students, and faculty 4,7,8 …”
Section: Introductionmentioning
confidence: 99%
“…However, it is also important to mention that self‐evaluation skills have shown to be inaccurate predictors of performance as students who underperform tend to evaluate themselves higher than faculty 39 . Accurate self‐evaluation is learned over time, which is evident as fourth‐year dental students' self‐assessment of operative procedures correlates more with faculty's assessment than that of second‐year dental students 40 …”
Section: Discussionmentioning
confidence: 99%
“…This study included several possible sources of error including the use of self-reporting with its possible overconfident and underconfident ratings. 18,19 However, recent literature suggests that self-assessment can be learned if supported by faculty, criteria, and multiple experiences, [20][21][22] as was the case with these respondents.…”
Section: Limitationsmentioning
confidence: 99%
“…Those with less competence have been found to rate their abilities higher than warranted, while those with more competence tend to score themselves lower. 18,19 However, recent studies have found congruence between students' self-ratings and those of faculty members, 20,21 particularly if self-assessment is supported by criteria and practice. 21,22 Dental accreditation standards in Canada 4 and the United States 5 acknowledge this by requiring evidence of students' abilities to self-evaluate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation